2010
DOI: 10.1038/jid.2010.159
|View full text |Cite
|
Sign up to set email alerts
|

Inversa Dystrophic Epidermolysis Bullosa Is Caused by Missense Mutations at Specific Positions of the Collagenic Domain of Collagen Type VII

Abstract: Abbreviations: Col7, collagen type VII; DEB, dystrophic epidermolysis bullosa; RDEB-I, inversa recessive dystrophic epidermolysis bullosa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 13 publications
5
32
0
Order By: Relevance
“…Recently, Chiaverini et al suggested that GSs located near the borders of collagenous subdomains exert different—that is, milder—pathogenic effects than GSs located in the centre of collagenous subdomains, and consequently result in RDEB-I 26. However, the combined genotypic data of our RDEB-I patients and those reported in the literature show that of the 13 glycine codons involved in RDEB-I, only 6/13 (46%) are located in the first three or last three Gly-X-Y triplets of their respective collagenous subdomain.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chiaverini et al suggested that GSs located near the borders of collagenous subdomains exert different—that is, milder—pathogenic effects than GSs located in the centre of collagenous subdomains, and consequently result in RDEB-I 26. However, the combined genotypic data of our RDEB-I patients and those reported in the literature show that of the 13 glycine codons involved in RDEB-I, only 6/13 (46%) are located in the first three or last three Gly-X-Y triplets of their respective collagenous subdomain.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the pruriginosa subtype of DEB, the causative COL7A1 mutations are usually known, but the exact cause of the pruriginosa phenotype has not been identified [Almaani et al, 2009;Schumann et al, 2008]. In addition, for the rare "inversa" subtype of RDEB, genotype-phenotype correlation is only now beginning to emerge [Chiaverini et al, 2010;Van den Akker et al, 2011].…”
Section: Dystrophic Epidermolysis Bullosa and The Type VII Collagen Gmentioning
confidence: 96%
“…2). Although the skin phenotype can be very mild in the inversa type, the mucosal and esophageal phenotype can be very severe, warranting regular and specific followup [Chiaverini et al, 2010;Van den Akker et al, 2011].…”
Section: Registry Analysis: Phenotypes Genotypes and Clinical Impactmentioning
confidence: 99%
“…A comprehensive revision of clinical features, immunostaining findings and literature, led to focus the attention in RDEB-I. RDEB-I was described in 1971 [20] and only a few cases have been reported to date [7,8]. The main trait is positive staining for type VII collagen at the blister roof and anchoring fibrils are variably reduced and hypoplastic.…”
Section: Et Etmentioning
confidence: 99%
“…RDEB mutations include nonsense, splice site, deletions or insertions, silent glycine substitutions and non-glycine missense mutations [6]. Very few cases of RDEB-I have been reported to date and about 29 genotypes have been recorded [7,8]. RDEB-I is characterized by blistering from birth and early infancy.…”
Section: Introductionmentioning
confidence: 99%